2009
DOI: 10.1088/0953-8984/21/37/373101
|View full text |Cite
|
Sign up to set email alerts
|

Molecular simulation of ionic liquids: current status and future opportunities

Abstract: Ionic liquids are salts that are liquid near ambient conditions. Interest in these unusual compounds has exploded in the last decade, both at the academic and commercial level. Molecular simulations based on classical potentials have played an important role in helping researchers understand how condensed phase properties of these materials are linked to chemical structure and composition. Simulations have also predicted many properties and unexpected phenomena that have subsequently been confirmed experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
397
1
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 385 publications
(422 citation statements)
references
References 126 publications
13
397
1
7
Order By: Relevance
“…[15][16][17] However, it was also shown that modified force fields with reduced (i.e., non-integer or fractional) charges on the ions considerably improve the MD results; [18,19] for details see the excellent review by Maginn. [20] When introducing such "effective charges" in computational chemistry, one might ask whether the value of this effective charge of a certain ion is a "real" quantity, implying some charge transfer between anion and cation, or whether it should be considered as a MD simulation parameter taking many body effects (e.g. polarisation) into account.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] However, it was also shown that modified force fields with reduced (i.e., non-integer or fractional) charges on the ions considerably improve the MD results; [18,19] for details see the excellent review by Maginn. [20] When introducing such "effective charges" in computational chemistry, one might ask whether the value of this effective charge of a certain ion is a "real" quantity, implying some charge transfer between anion and cation, or whether it should be considered as a MD simulation parameter taking many body effects (e.g. polarisation) into account.…”
Section: Introductionmentioning
confidence: 99%
“…by theoretical/molecular simulation methods [12][13][14][15][16][17][18][19][20] and several predictive models have been proposed. 11,[21][22][23][24] Currently it is well accepted that ILs are highly structured fluids in which the ion pairs arrange themselves into polar and non-polar domains.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] In this context, imidazolium acetate based ILs were proposed as systems able to capture comparatively to other ionic liquids, unusual amounts of carbon dioxide. 12,13 A number of investigations by us and others have shown that carbon dioxide dissolved in dried 1-butyl-3-methylimidazolium acetate [Bmim] [Ac] a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%